Tourists’ Perceptions of Geotourism Development in Sumedang: A Qualitative Social Tourism Study - Irena Novarlia (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Sumedang Regency, rich in geological and cultural heritage, holds significant potential for geotourism development, yet faces challenges in delivering meaningful visitor experiences. This study aims to explore tourists’ perceptions of geotourism development in Sumedang from a social tourism perspective, focusing on their emotional, cognitive, and cultural interactions with key sites. Using a qualitative case study approach, data were collected through in-depth interviews with eighteen tourists, participatory observations, and visual documentation, including photographs and visual interpretations. Analysis revealed three main themes: the natural beauty of sites like Mount Tampomas and Jatigede Reservoir lacks educational narratives, limited infrastructure hinders access and diminishes satisfaction, and tourists desire greater involvement with local culture and narratives. These findings highlight the need for enhanced interpretive media and community engagement to transform superficial experiences into meaningful ones. The study, limited to domestic tourists and a short observation period, concludes that Sumedang’s geotourism can thrive by integrating geological education, improving infrastructure, and empowering local communities as storytellers. These insights contribute to understanding geotourism as a socially constructed process and offer practical strategies for sustainable destination development in Sumedang.